Property Management Services of Different Village Clubhouses: Basis for an Improved Quality Model (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to assess the property management services of Village Clubhouses as the basis for an improved quality management model. It sought to establish the profile of the customers that will represent the sample in the study, that helped identify the level of perception and compare the results to the level of expectation and the gaps of service quality using the SERVQUAL framework. The study determined the significant difference between the level of expectation and level of perception of service quality, respectively. The result showed that the level of perception was low and that expectations were not met after the service have been experienced. The levels of perception vary based on their interest, the number of usages, and the facility being used; and the level of perception changes over time. The current findings call for emergent attention from the property management services company to take appropriate service performance and physical resource structure and monitor such to improve service quality to customers and employee performance.